(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of profitability, leverage, liquidity, company age and company size on the accuracy of submitting financial reports to pharmaceutical companies listed on the Indonesia Stock Exchange for the 2016- 2020 period. The research method uses quantitative methods by performing multiple linear regression between the variables of profitability, leverage, liquidity, company age and company size on the accuracy of financial statement submission. The sample in this study was determined by purposive sampling. This study concludes that the variables of profitability, leverage and liquidity have no effect on the accuracy of submitting financial statements. While the age of the company and the size of the company affect the accuracy of the submission of financial statements. The value of Adjusted R Square (R²) indicates a value of 0.202. It identified that all independent variables (profitability, leverage, liquidity, firm age and firm size) were able to influence the dependent variable (accuracy in submitting financial statements) by 20.2%.